The Siberian Branch of the Shibanid Dynasty in Sh. Marjani’s Studies - Maslyuzhenko D.N. (Золотоордынское обозрение, 2019)
Objectives and research materials: In 1885, Shihabuddin Marjani wrote the work “Mustafa al-Akhbar fi ahwal Kazan va Bulgar” (“The Mine of Information about Events in Kazan and Bulghar”). By analyzing chapters of the history on the Siberian branch of the Shibanid dynasty, the author of the present article aims to identify the main sources for the hypotheses proposed by S. Marjani. In the part of the work published in Russian, there are several stories related to representatives of the branch of the Shibanid dynasty who were enthroned in Tyumen and Siberia. Stories about them are scattered in various sections: “Section about the Toqtamishids”, “Section about the New State with the Capital in Kazan”, “Section about the Kasimov Khanate in the Lands of Kirman”, “Section about the Siberian Khans”. In addition, some information is available in the “Section about the Sheibanid Khans” and “Section about the Sheibanids Who Ruled in Mawarannahr”. Results and novelty of the research: A comparison of Marjani’s accounts with the sources published in Russian at that time allows us to suggest that Marjani could have made use of “The Genealogical Tree of the Turks” by Abu-l-Ghazi, the “Sheibaniade” by an unknown author and published in Kazan in 1849 by I. Berezin, the “Collection of Materials Relating to the History of the Golden Horde” by V. Tizengauzen (Volume I. Extracts from Arabic sources), and “Studies of the Kasimov Tsars and Princes” by V.V. Velyaminov-Zernov. With a certain degree of probability, he also could have used the work, “Mukim-Khan’s history” by Muhammad Yusuf Munshi. In such a case, Marjani was apparently the first historian in the Russian milieu who used Munshi’s text and briefly reviewed the history of the formation and collapse of the Uzbek khanate of Abu al-Khair. Although suffering from certain factual flaws, the work of Marjani contained important information on the history of the Shibanids. Moreover, in some cases, the author’s assumptions were ahead of the historical scholarship of his time; for example, regarding the khan’s titles of Ali and Ishim. This observation indicates the need for further research into the sources used by this author.